Comparison of Diagnostic Yield and Safety between Semirigid Pleuroscopic Cryobiopsy and Forceps Biopsy for Undiagnosed Pleural Effusion. (20th December 2019) - Lee, Chung-Shu; Li, Shih-Hong; Chang, Chih-Hao; Chung, Fu-Tsai; Chiu, Li-Chung; Chou, Chun-Liang; Wang, Chih-Wei; Lin, Shu-Min
Abstract : For undiagnosed pleural effusion, diagnostic yields and safety were similar between pleuroscopic cryobiopsy and forceps biopsy, but cryobiopsy obtained a larger pleural tissue sample than forceps biopsy.